Progress in the Chemistry of Organic Natural Products 105 - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi (Progress in the Chemistry of Organic Natural Products, 2017)
The first contribution reviews the occurrence of xanthine alkaloids in the plant kingdom and the elucidation of the caffeine biosynthesis pathway, providing details of the N-methyltransferases, belonging to the motif B' methyltransferase family which catalyze three steps in the four step pathway leading from xanthosine to caffeine. The second contribution in this book provides a background on the molecule and related compounds and update knowledge on the most recent advances in Iboga alkaloids. The third contribution presents a comprehensive analysis of frequently occurring errors with respect to 13C NMR spectroscopic data and proposes a straightforward protocol to eliminate a high percentage of the most obvious errors.